Aminomethylene peptide nucleic acid (am-PNA): synthesis, regio-/stereospecific DNA binding, and differential cell uptake of (alpha/gamma,R/S)am-PNA analogues - Mitra, Roopa; Ganesh, Krishna N. (Journal of Organic Chemistry, 2012)
Inherently chiral, cationic am-PNAs having pendant aminomethylene groups at alpha(R/S) or gamma(S) sites on PNA backbone have been synthesized. The modified PNAs are shown to stabilize duplexes with complementary cDNA in a regio- and stereo-preferred manner with gamma(S)-am PNA superior to alpha(R/S)-am PNAs and alpha(R)-am PNA better than the alpha(S) isomer. The enhanced stabilization of am-PNA:DNA duplexes is accompanied by a greater discrimination of mismatched bases. This seems to be a combined result of both electrostatic interactions and conformational preorganization of backbone favoring the cDNA binding. The am-PNAs are demonstrated to effectively traverse the cell membrane, localize in the nucleus of He La cells, and exhibit low toxicity to cells.